Nurse ethical sensitivity: An integrative review - Milliken, Aimee (Nursing ethics, 2018)
Background:Ethical sensitivity has been identified as a foundational component of ethical action. Diminished or absent ethical sensitivity can result in ethically incongruent care, which is inconsistent with the professional obligations of nursing. As such, assessing ethical sensitivity is imperative in order to design interventions to facilitate ethical practice and to ensure nurses recognize the nature and extent of professional ethical obligations.Aim:To review and critique the state of the science of nurse ethical sensitivity and to synthesize findings across studies.Research design:Whittemore and Knafl’s revised framework for integrative reviews guided the analysis.Research context and data sources:A comprehensive, computer-assisted search of literature published in Cumulative Index of Nursing and Allied Health Literature and PubMed was performed. A systematic approach was used to extract, reduce, and synthesize the data.Findings:Four major conceptualizations of ethical sensitivity emerged from the literature. A sample of 25 reports met inclusion criteria, including 17 empirical reports and 8 theoretical reports.Discussion:Despite the existence of a concept analysis and a validated tool, ethical sensitivity remains a highly theoretical concept with multiple, and at times competing, conceptualizations. Ethical sensitivity has been assessed extensively in the context of ethical dilemmas; however, little attention has been paid to the way the concept operates in day-to-day practice.Conclusion:Future research should focus on better ways to operationalize and assess the concept, with particular attention to nurse awareness of the ethical content of everyday practice.